Peran & Tantangan Notaris Perbankan Syariah dalam Pengembangan Perekonomian di Indonesia - Ro’fah Setyowati (Jurnal Hukum Ekonomi Islam, 2019)
Notary has a strategic position in making Islamic banking contracts. This is because the Notary is responsible for the correctness of the contract construction to fulfill the terms of the agreement, as well as sharia principles. This study is intended to analyze the legal consequences that arise in the relationship between the Notary profession and the Islamic banking industry. It is important to find opportunities and challenges of Notaries in supporting the development of Islamic economics in Indonesia. This study uses a philosophical, juridical and empirical approach. The results of the analysis show that the need for a notary who has sharia competence in Islamic banking is an urgent matter. In addition, the opportunities and challenges for sharia-compliant notaries are as great. This is due to the fact that the potential of the Islamic banking market is still very large, but there are also many technological developments with various problems. For this reason, Islamic competent notaries need to be confident that the non-religious transaction concept is the design of Allah SWT, the Creator of man, so that it needs to be studied, practiced, disseminated and oriented towards finding solutions if there are still obstacles in its implementation. Keywords: opportunities, notaries, Islamic banking, Indonesia. Abstrak Notaris mempunyai posisi strategis dalam pembuatan akad perbankan syariah. Hal tersebut karena Notaris bertanggungjawab terhadap kebenaran konstruksi akad agar terpenuhi syarat-syarat perjanjian, serta prinsip-prinsip syariah. Kajian ini dimaksudkan untuk menganalisis konsekwensi hukum yang timbul dalam hubungan antara profesi Notaris dengan industri perbankan syariah. Hal tersebut penting untuk menemukan peluang dan tantangan Notaris dalam mendukung pengembangan ekonomi syariah di Indonesia. Kajian ini menggunakan pendekatan filosofis, yuridis dan empiris. Hasil analisisnya diketahui bahwa kebutuhan terhadap notaris yang berkempetensi syariah pada perbankan syariah merupakan hal mendesak. Selain itu, peluang dan tantangan bagi notaris berkompensi syariah sama besar. Hal tersebut disebabkan, potensi pasar perbankan syariah masih sangat besar, namun perkembangan teknologi dengan berbagai permasalahannya juga banyak. Untuk itu, notaris berkompetensi syariah perlu sikap yakin bahwa konsep traksaksi non ribawi merupakan desain dari Alloh SWT, Sang Pencipta manusia, sehingga perlu terus dipelajari, diamalkan, disebaruaskan dan berorientasi mencari solusi jika masih terdapat kendala dalam pelaksanaannya. Kata kunci : peluang-tantangan, notaris, perbankan syariah, Indonesia.